Prevalence and risk factors associated with Babesia bovis infection in Crioula Lageana cattle - Casa, Mariana da Silva; Vettori, Julio de Matos; de Souza, Ketriane Mota; Todeschini, Paulo Ricardo Benetti; Miletti, Luiz Claudio; Vogel, Carla Ivane Ganz; Lima, André Luiz Ferreira; Fonteque, Joandes Henrique (The Journal of Infection in Developing Countries, 2023)
Introduction: Bovine babesiosis caused by the protozoan Babesia bovis is a worldwide disease and causes great economic damage to livestock. There are no studies on the epidemiology of this disease in native breeds such as Crioula Lageana cattle raised in the South of Brazil. Methodology: DNA samples from 311 animals were amplified by polymerase chain reaction (PCR) for the identification of the gene rap-1 (Rhoptry Associated Protein 1) from B. bovis. An epidemiological questionnaire was used to determine the risk factors associated with infection. Results: The prevalence of B. bovis infection was 72% (224/311). Age and tick infestation affected infection. The factors associated with infection were the breeding objective (p = 0.042; CI = 0.746-0.995; OR = 0.861), contact of cattle with other animal species (p = 0.002; CI = 0.517-0.860; OR = 0.484), absence of tick control (p = < 0.001; CI = 0.074-0.480; OR = 0.188) and timing of tick treatment (p = 0.026; CI = 0.673-0.975; OR = 0.810), and these were considered to be factors that can protect against the disease. Conclusions: The Crioula Lageana cattle breed has near enzootic stability with regards to B. bovis infection.